Развитие транспортной логистики в Украине - Гофштейн, Е. И. (НТУ "ХПИ", 2012)
В работе рассматриваются современные проблемы транспортной логистики в Украине и пути их решения.

The current problems of transport logistics in Ukraine and ways of their solution are described in the present paper.
Keywords: перевозки; состав подвижной; страхование груза; transport industry; transportations; rolling stock; insurance of load